Infrastructure and Trade Preferences for the Livestock Sector : Empirical Evidence from the Beef Industry in Africa - Iimi, Atsushi (World Bank, Washington, DC, 2012)
Trade preferences are expected to facilitate global market integration and offer the potential for rapid economic growth and poverty reduction for developing countries. But those preferences do not always guarantee sustainable external competitiveness to beneficiary countries and may risk discouraging their efforts to improve underlying productivity. This paper examines the EU beef import market where several African countries have been granted preferential treatment. The estimation results suggest that profitability improvement achieved by countries under the Cotonou protocol compares unfavorably with the returns to nonbeneficiary countries in recent years. Rather, it shows that public infrastructure, such as paved roads, has an important role in lowering production costs and thus increasing external competitiveness and market shares.